1979
DOI: 10.1021/ac50049a027
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of temperature, salt concentration, and pH on head space analysis for isolating volatile trace organics in aqueous environmental samples

Abstract: A systematic approach Is presented for the Isolation and quantification of volatile trace organics from aqueous solutions by head space analysis. Fundamental information is obtained on the partition process for a multiple solute system consisting of model compounds under varying aqueous matrix conditions, i.e., pH, temperature, and salt addition. Interactive effects between parameters are quantitatively shown by the use of the thermodynamic equilibrium partition coefficient. A general optimum head space isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…In fact, to this end, many studies have used a certified soil material with known concentrations of PAHs together with a reference biochar sample. For headspace methods, commonly employed for the identification of VOCs, vial temperature and equilibration time are the most crucial parameters for method development (Friant & Suffet, 1979;Penton, 1992). A natural soil containing 15 PAHs with concentrations ranging from 1.14 to 12.9 mg kg À1 was used together with an internal reference biochar sample (industrial-scale slow pyrolysis orchard prunings biochar).…”
Section: Methods Validation Using Soil and Biochar Samplesmentioning
confidence: 99%
“…In fact, to this end, many studies have used a certified soil material with known concentrations of PAHs together with a reference biochar sample. For headspace methods, commonly employed for the identification of VOCs, vial temperature and equilibration time are the most crucial parameters for method development (Friant & Suffet, 1979;Penton, 1992). A natural soil containing 15 PAHs with concentrations ranging from 1.14 to 12.9 mg kg À1 was used together with an internal reference biochar sample (industrial-scale slow pyrolysis orchard prunings biochar).…”
Section: Methods Validation Using Soil and Biochar Samplesmentioning
confidence: 99%
“…To date, many studies have been conducted to evaluate the effect of such substances on the analysis of the volatile fraction of liquids such as apple juice [21], milk [22] or model aqueous solutions [23][24][25][26][27]. These investigations have shown that adding hygroscopic salts increases the vapor pressure and therefore the concentration of the volatile substances in the headspace of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Its application can be expanded to the extraction of moderately polar substances by the addition of salt (such as Na2SO4) to a solute-poor solution (Friant & Suffet, 1979). Such treatments can shift the vapour-phase partitioning into the desired direction.…”
Section: Resultsmentioning
confidence: 99%